The Correlation Between Caries Severity and Dental Pain Stress Level in the Community of Sucopangepok Village, Jelbuk Subdistrict, Jember Regency - Yani, Ristya Widi Endah; Handayani, Ari Tri Wanadyo; Kiswaluyo, Kiswaluyo (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: The results of the Basic Health Research in 2018 show that the prevalence of caries in Indonesia is high (88.8%), and the prevalence of active caries in East Java is also high (42.4%). One of the consequences of untreated caries is stress dental pain due to toothache which has an impact on the quality of life.Method: Observational analytical research with a cross-sectional approach on people aged 17 years and above was conducted on February 2023 – March 2023. A total of 318 respondents uses simple random sampling. The variable of the research are dental caries severity (using the PUFA index) and dental pain stress (using a modification of the Kessler Psychological Distress Scale questionnaire with Perceived Stress Scale).Result: The data obtained were tabulated and analyzed with descriptive statistics and continued with the Spearman correlation test. 36% of respondents age 26-35 years, 57.23% were female. 41.82% have primary school education and work as housewives and farmers. The average caries severity is 2.6 categorized as high with dental pain stress categorized as medium. Spearman correlation test show significance (p) <0.05 which means there is a correlation between caries severity level and dental pain stress.Conclusion: There is a relationship between caries severity and stress dental pain